The Effectiveness of Pre-Service English Teachers’ Collaborative Genre-Based Writing Feedback - Didik Rinan Sumekto (Lingua Cultura, 2017)
This study investigated the collaborative genre-based effectiveness among the pre-service English teachers (PSETs). Data collection used the genre-based writing feedback observation upon its reflection and instruction and need analysis questionnaire. The data analysis used multivariate statistics method to generalize the writing tests. The findings show that the PSETs’ feedback supported the interaction, accountability, and interdependence. These aspects are due to the collaborative participation in groups, in which the PSETs work with the flexibility, entirely performed the quality, and contributed in positive attitude during the meetings and assignments. The feedback emphasiz the learning improvement within the formative reflection through the general linear model (GLM) repeated measures analysis, where F=6,114 and p<0,01. This study concludes that the collaborative genre-based writing feedback has the positive response from the PSETs. The determinant ranges gains in between 85% to 90% after a series of genre-based writing lectures were conducted.